2020
DOI: 10.3390/ijerph17207518
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumer Subsidy on Green Technology Innovations for Vehicles and Environmental Impact

Abstract: In the pressure of excessive resource consumption and serious environmental pollution, governments provide various consumer subsidies to promote sales of energy-saving vehicles, including the energy-saving fuel vehicle (FV) and the pure electric vehicle (EV) in the automobile industry. Utilizing a Hotelling model, this paper explores two competing firms’ decisions on the selection of green technology innovations for vehicles, namely producing either the energy-saving FV or the pure EV, while the two vehicles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The subsequent ndings would provide a more detailed understanding of how various PM 2.5 sources affect human health. Such information could be used for government-level policy development regarding tra c-related air pollution, such as creating additional regulations on vehicle emissions, including European Emission Standards 69 , subsidizing electric vehicles 70 , establishing or revising low-emission zones within cities 71,72 , or improving protocols for tires, brakes, and road surfaces. Cities can also prioritize reducing tra c overall by investing in public transportation options and establishing safe, convenient active transportation options, such as a networks of bike lanes and well-maintained pedestrian sidewalks 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent ndings would provide a more detailed understanding of how various PM 2.5 sources affect human health. Such information could be used for government-level policy development regarding tra c-related air pollution, such as creating additional regulations on vehicle emissions, including European Emission Standards 69 , subsidizing electric vehicles 70 , establishing or revising low-emission zones within cities 71,72 , or improving protocols for tires, brakes, and road surfaces. Cities can also prioritize reducing tra c overall by investing in public transportation options and establishing safe, convenient active transportation options, such as a networks of bike lanes and well-maintained pedestrian sidewalks 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [23] studied competition between two green supply chains and found that competition for carbon emissions would reduce total optimization cost and carbon emissions. Zhang et al [24] studied dynamic pricing strategy and greening issues in a two-stage dual-channel green supply chain. Jie et al [25] studied the impact of manufacturers' fairness concerns and retailers' sales efforts on decision-making in green closedloop supply chains.…”
Section: Green Supply Chainmentioning
confidence: 99%
“…They found that while subsidies help promote the use of solar panels, it exacerbates social surpluses when the value of carbon reductions does not exceed market prices. It was demonstrated by Zhang et al [16] that although consumer subsidies are always beneficial to green technology innovation in the automotive industry, under certain conditions, it may lead to a reduction in consumer surplus and corporate profits. Combining the risk aversion characteristics of retailers, Cao et al [17] compared and analyzed the differences in the impact of non-subsidy strategy, manufacturer subsidy strategy, and consumer subsidy strategy on decision-making.…”
Section: Introductionmentioning
confidence: 99%